Effects of Rivaroxaban on Platelet Activation and Platelet–Coagulation Pathway Interaction: In Vitro and In Vivo Studies. (November 2015) - Perzborn, Elisabeth; Heitmeier, Stefan; Laux, Volker
Introduction: Activation of coagulation and platelets is closely linked, and arterial thrombosis involves coagulation activation as well as platelet activation and aggregation. In these studies, we investigated the possible synergistic effects of rivaroxaban in combination with antiplatelet agents on thrombin generation and platelet aggregation in vitro and on arterial thrombosis and hemostasis in rat models. Materials and Methods: Thrombin generation was measured by the Calibrated Automated Thrombogram method (0.5 pmol/L tissue factor) using human platelet-rich plasma (PRP) spiked with rivaroxaban (15, 30, or 60 ng/mL), ticagrelor (1.0 µg/mL), and acetylsalicylic acid (ASA; 100 µg/mL). Tissue factor-induced platelet aggregation was measured in PRP spiked with rivaroxaban (15 or 30 ng/mL), ticagrelor (1 or 3 µg/mL), or a combination of these. An arteriovenous (AV) shunt model in rats was used to determine the effects of rivaroxaban (0.01, 0.03, or 0.1 mg/kg), clopidogrel (1 mg/kg), ASA (3 mg/kg), and combinations on arterial thrombosis. Results: Rivaroxaban inhibited thrombin generation in a concentration-dependent manner and the effect was enhanced with ticagrelor and ticagrelor plus ASA. Rivaroxaban and ticagrelor also concentration-dependently inhibited tissue factor-induced platelet aggregation, and their combination increased the inhibition synergistically. In the AV shunt model, rivaroxaban dose-dependently reduced thrombus formation. Combining subefficacious or weakly efficacious doses of rivaroxaban with ASA or ASA plus clopidogrel increased the antithrombotic effect. Conclusion: These data indicate that the combination of rivaroxaban with single or dual antiplatelet agents works synergistically to reduce platelet activation, which may in turn lead to the delayed/reduced formation of coagulation complexes and vice versa, thereby enhancing antithrombotic potency.